A weak lithium ion solvated solid-state polymer electrolyte containing urea-based side chains and a preparation method and application thereof

CN122968425APending Publication Date: 2026-10-23SHANGHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611062711.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

液态电解质作为正极与负极之间的锂离子迁移介质,虽具有优异的离子电导率(1-10 mS cm-1),但存在电解液泄漏、易燃等安全隐患

Benefits of technology

(1)本发明针对现有固态聚合物电解质中聚合物链段对锂离子强溶剂化作用限制迁移速率的瓶颈,提供了一种含有脲基侧链的弱锂离子溶剂化固态聚合物电解质改性方法。该聚合物电解质包括聚合物基质以及分布在其中的锂盐;聚合物基质由侧链单体、碳酸乙烯亚乙酯、乙二醇二甲基丙烯酸酯经原位聚合交联形成。所述固态聚合物电解质的侧链上具有由酯基氧、脲基氧以及苯基/氟苯基等组成的多个弱溶剂化基团,能够协同降低聚合物链段对锂离子的吸附能,削弱强溶剂化作用,同时增强对锂盐阴离子的锚定作用,从而有效提升固态聚合物电解质的离子迁移数和离子电导率,并最终提高电池的循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968425A_ABST
    Figure CN122968425A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of weak lithium ion solvated solid-state polymer electrolyte containing urea-based side chain and its preparation method and application, the polymer electrolyte includes polymer matrix and the lithium salt distributed therein;Polymer matrix is formed by side chain monomer, ethylene carbonate, ethylene glycol dimethyl methacrylate crosslinking in situ polymerization;The structural formula of side chain monomer is as shown in general formula (I): general formula (I);Wherein, R1 include any one of phenyl, fluorophenyl, alkyl.This solid-state polymer electrolyte of the present application has reduced the proportion of lithium ion solvated structure polymer segment, and the solid-state polymer electrolyte has higher ionic conductivity and lower activation energy, and the anchoring effect of lithium salt anion is stronger, effectively improves the ion migration number of solid-state polymer electrolyte.The synthesis of side chain monomer is simple, and the solid-state polymer electrolyte uses thermal initiation in-situ polymerization method, with low cost, high equipment applicability, with the potential for practical production and use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery electrolyte technology, and in particular to a weak lithium-ion solvated solid polymer electrolyte containing urea side chains, its preparation method, and its application. Background Technology

[0002] Currently, lithium batteries are widely used in consumer electronics such as electric vehicles, drones, and mobile phones, and their application scenarios will further expand. However, "power anxiety" and "safety anxiety" have fueled great enthusiasm for developing batteries with higher energy density, faster charging speeds, and greater safety. Liquid electrolytes, as the lithium-ion migration medium between the positive and negative electrodes, possess excellent ionic conductivity (1-10 mS / cm). -1 However, solid-state lithium metal batteries (SLMs) pose safety hazards such as electrolyte leakage and flammability. Therefore, polymer-based solid-state lithium metal batteries, which combine excellent safety with high energy density, have emerged. Compared to all-solid-state electrolytes such as halides and oxides, polymer electrolytes offer more balanced overall performance: their inherent flexibility provides excellent interfacial compatibility, buffering volume changes in the electrodes during charging and discharging; replacing the original separator and liquid electrolyte with a thinner, lighter polymer electrolyte improves battery safety; and their manufacturing process is highly compatible with existing production processes, reducing the cost required for large-scale commercial manufacturing. Summary of the Invention

[0003] The purpose of this invention is to provide a weakly lithium-ion solvated solid polymer electrolyte containing urea-based side chains, its preparation method, and its application. The solid polymer electrolyte has multiple weakly solvated groups on its side chains, which can reduce the strong solvation effect of polymer chain segments on lithium ions and enhance the anchoring effect on lithium salt anions, thereby effectively improving the ion transference number and ionic conductivity of the solid polymer electrolyte and improving the cycle stability of the battery.

[0004] The objective of this invention can be achieved through the following technical solutions: On one hand, the present invention provides a weak lithium-ion solvable solid polymer electrolyte containing urea side chains, comprising a polymer matrix and a lithium salt distributed therein; The polymer matrix is ​​formed by in-situ polymerization and crosslinking of side-chain monomers, ethylene ethylene carbonate, and ethylene glycol dimethacrylate; the structural formula of the side-chain monomers is shown in general formula (I): General formula (Ⅰ); R1 includes any one of phenyl, fluorophenyl, and alkyl.

[0005] Preferably, R1 includes either phenyl or fluorophenyl.

[0006] More preferably, R1 is a fluorophenyl.

[0007] Secondly, the present invention provides a method for preparing the weakly lithium-ion solvated solid polymer electrolyte containing urea side chains, comprising the following steps: S1. Preparation of side-chain monomers: Isoethyl methacrylate and amine monomers are dissolved in an organic solvent, a catalyst is added to catalyze the reaction, deionized water is added to quench the reaction after the reaction is completed, the product is collected by recrystallization, and the side-chain monomers are obtained by freeze drying. S2. Preparation of solid polymer electrolyte precursor solution: Ethylene carbonate, ethylene glycol dimethacrylate and the side chain monomer obtained in step S1 are mixed evenly, and then lithium salt and azobisisobutyronitrile are added and mixed evenly to obtain the solid polymer electrolyte precursor solution. S3. In-situ polymerization to form solid polymer electrolyte: The solid polymer electrolyte precursor solution is injected into the lithium-ion battery, and after standing for a period of time, an in-situ polymerization and cross-linking reaction is carried out by thermal initiation to form the solid polymer electrolyte in-situ inside the lithium-ion battery.

[0008] Preferably, in step S1, the amine monomer includes any one of benzylamine, 4-fluorobenzylamine, or alkylamine.

[0009] More preferably, in step S1, the alkylamine is n-propylamine.

[0010] More preferably, in step S1, the amine monomer is either benzylamine or 4-fluorobenzylamine.

[0011] More preferably, in step S1, the amine monomer is 4-fluorobenzylamine.

[0012] Preferably, in step S1, the organic solvent includes one or more of dichloromethane and acetonitrile.

[0013] Preferably, in step S1, the catalyst includes one or more of triethylamine and dibutyltin dilaurate.

[0014] Preferably, in step S1, the molar ratio of isocyanate methacrylate to amine monomer is 1-5:1-5.

[0015] More preferably, in step S1, the molar ratio of isocyanate methacrylate to amine monomer is 1:1.

[0016] Preferably, in step S1, the catalyst is 0.1-10 wt% of the sum of the mass of isocyanate methacrylate and amine monomers.

[0017] More preferably, in step S1, the catalyst is 1 wt% of the sum of the mass of isocyanate methacrylate and amine monomers.

[0018] Preferably, in step S1, the reaction temperature is 0-30℃ and the reaction time is 6-12 h.

[0019] Preferably, in step S1, the solvent used for recrystallization is a mixed solvent of dichloromethane and n-hexane, wherein the volume ratio of dichloromethane to n-hexane is 1-4:1-4.

[0020] Preferably, in step S1, the freeze-drying temperature is -20 to 80°C and the time is 5 to 24 hours.

[0021] Preferably, in step S2, the molar ratio of ethylene carbonate: ethylene glycol dimethacrylate: side chain monomer is 100:1-5:0-5.

[0022] Preferably, in step S2, the mass ratio of the lithium salt to the solid polymer electrolyte precursor solution is 1:1-10, and the mass ratio of the azobisisobutyronitrile to the solid polymer electrolyte precursor solution is 0.01-0.1:1.

[0023] Preferably, in step S2, the lithium salt includes any one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalateborate (LiDFOB), lithium bis(difluorosulfonyl)imide (LiFSI), lithium bis(oxalateborate)borate (LiBOB), and lithium tetrafluoroborate (LiBF4).

[0024] More preferably, in step S2, the lithium salt is lithium bis(trifluoromethanesulfonylimide).

[0025] Preferably, in step S3, the volume of the polymer electrolyte added to the lithium-ion battery is 20-50 μL.

[0026] Preferably, in step S3, the settling time is 1-24 hours.

[0027] Preferably, in step S3, the temperature for thermal initiation of the in-situ polymerization crosslinking reaction is 50-80°C, and the time is 6-10 hours.

[0028] Thirdly, the present invention provides an application of the weak lithium-ion solvated solid polymer electrolyte containing urea side chains in lithium-ion batteries.

[0029] Preferably, the lithium-ion battery includes a negative electrode shell, a lithium negative electrode sheet, a solid polymer electrolyte, a separator, a solid polymer electrolyte, a positive electrode sheet, and a positive electrode shell, which are stacked sequentially.

[0030] Preferably, the lithium-ion battery is prepared by dripping a solid polymer electrolyte precursor solution between the lithium sheet and the separator, and between the separator and the positive electrode sheet, respectively, encapsulating and allowing it to stand, and then performing in-situ polymerization initiated by heat to obtain the lithium-ion battery.

[0031] Preferably, the effective working area of ​​the lithium sheet is 1.4-1.8 cm². 2 The effective working area of ​​the positive electrode is 1.0-1.4 cm². 2 .

[0032] Preferably, the volume of the solid polymer electrolyte precursor solution added to the lithium-ion battery is 20-50 μL.

[0033] The side-chain monomers used in this invention endow the polymer with weak solvation properties for lithium ions. Taking a side-chain monomer with R1 as phenyl / fluorophenyl as an example, the ester oxygen, urea oxygen, and phenyl / fluorophenyl groups in its side chain can all interact with lithium ions. Specifically, the adsorption energies of the ester oxygen and urea oxygen for lithium ions are -4.19 eV, the benzene ring for -3.40 eV, and the fluorine atom for -1.72 eV. In comparison, the adsorption energies of bimolecular ethylene carbonate and monomolecular ethylene carbonate for lithium ions are -4.50 eV and -2.31 eV, respectively. Therefore, the adsorption energies of each interaction site in the side-chain monomer of this invention generally show a decreasing trend, especially the phenyl and fluorophenyl groups exhibiting weaker lithium-ion solvation capabilities. Molecular dynamics simulations show that in the four electrolyte groups, the lithium-ion solvation structure of the system without side-chain monomers contains 3.08 ethylene carbonate atoms and 1.80 TFSI atoms. - After adding a side-chain monomer containing an alkane segment, its lithium-ion solvated structure contains 2.37 ethylene carbonate esters and 1.60 TFSI esters. - After adding a side-chain monomer containing a phenyl segment, its lithium-ion solvated structure contains 2.34 ethylene carbonate esters and 1.65 TFSI esters. - After adding a side-chain monomer containing a fluorinated phenyl segment, its lithium-ion solvated structure contains 2.26 ethylene carbonate esters and 1.74 TFSI esters. - It can effectively dissociate polymer segments in lithium-ion solvated structures and introduce anions. This is a key innovation that distinguishes this invention from existing technologies.

[0034] Furthermore, the multiple weak solvation groups in the side-chain monomers do not function in isolation, but rather work synergistically to regulate the coordination environment of lithium ions, reducing the binding strength between lithium ions and polymer segments, promoting lithium ion decoupling and migration, thereby improving ion transport efficiency. This mechanism also applies to monomers containing alkane segments and phenyl side-chain structures, both of which can optimize lithium ion migration behavior through multi-site weak solvation synergistic effects. Therefore, this invention does not simply introduce alkane, phenyl, or fluorine-containing groups, but rather constructs multi-site weak solvation side-chain structures composed of ester oxygen, urea oxygen, and alkane / phenyl / fluorophenyl groups, achieving the synergistic effect of multiple weak coordination sites. This promotes lithium ion desolvation and rapid migration while ensuring lithium salt dissociation capability, an effect not previously known or anticipated in existing technologies.

[0035] The purpose of introducing fluorinated alkyl groups in existing technologies is to form a lithium fluoride-rich interfacial film during battery cycling, thereby improving the stability of the electrode / electrolyte interface and suppressing lithium dendrite growth. These technologies focus on the composition and stability of the interfacial film. In contrast, this invention addresses the issue of ion migration efficiency within the polymer by constructing a multi-site weakly solvated side chain structure composed of ester oxygen, urea oxygen, and phenyl / fluorophenyl groups.

[0036] This invention addresses the strong solvation problem in lithium-ion transport within polymer electrolytes by designing a multi-site weak solvation side chain structure composed of ester oxygen, urea oxygen, and phenyl or fluorophenyl groups. This reduces the polymer's adsorption capacity for lithium ions, regulates the local coordination environment of lithium ions, and promotes decoupling and migration, thereby improving the ion transport efficiency of the polymer electrolyte. Furthermore, in this invention, phenyl or fluorophenyl groups act as weak coordination sites, participating in the coordination regulation of lithium ions and forming a multi-site weak solvation system together with ester oxygen and urea oxygen. The synergistic effect among these sites collectively reduces the binding strength of lithium ions, promoting their decoupling and migration. This synergistic effect is a key reason for the excellent ion transport performance achieved in this invention. In addition, theoretical calculations further confirm that ester oxygen, urea oxygen, phenyl, and fluorophenyl groups in the side chain all exhibit weak lithium-ion adsorption capacity. Phenyl and fluorophenyl groups can further reduce the adsorption energy of lithium ions, effectively promoting the desolvation process. The above technical effects stem from the synergistic design of the overall side chain structure, rather than being achieved by simply replacing a single substituent.

[0037] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention addresses the bottleneck of lithium-ion migration rate limitation caused by the strong solvation effect of polymer segments on lithium ions in existing solid polymer electrolytes by providing a method for modifying a weakly lithium-ion solvated solid polymer electrolyte containing urea-based side chains. The polymer electrolyte comprises a polymer matrix and lithium salts distributed therein; the polymer matrix is ​​formed by in-situ polymerization and crosslinking of side-chain monomers, ethylene ethylene carbonate, and ethylene glycol dimethacrylate. The side chains of the solid polymer electrolyte have multiple weakly solvated groups composed of ester oxygen, urea oxygen, and phenyl / fluorophenyl groups, which can synergistically reduce the adsorption energy of polymer segments on lithium ions, weaken the strong solvation effect, and simultaneously enhance the anchoring effect on lithium salt anions, thereby effectively improving the ion transport number and ionic conductivity of the solid polymer electrolyte, and ultimately improving the cycle stability of the battery.

[0038] (2) The modified solid polymer electrolyte of this invention achieves a significant improvement in ion transport performance. Theoretical calculations and molecular dynamics simulations show that the adsorption energies of lithium ions by ester oxygen, urea oxygen, benzene ring, and fluorine atoms in the side chain are all lower than the solvation energy of ethylene carbonate. After introducing phenyl or fluorophenyl side chains, the average coordination number of ethylene carbonate in the lithium ion solvation structure decreases from 3.08 to 2.26-2.37, indicating that the polymer chain segments are effectively dissociated, and the lithium ion decoupling migration is smoother. At the same time, the fluorophenyl side chain, through the synergistic effect of hydrogen bonds in the urea group and the electron-deficient π electron cloud, can enhance the ion transport performance of TFSI. - To achieve effective anchoring, it is necessary to target TFSI. - The adsorption energy reaches -1.34 eV, which is significantly stronger than that of ethylene carbonate for TFSI. - The adsorption energy (-0.95 eV) indicates that the side-chain structure of this invention has a strong anchoring ability for lithium salt anions, further promoting lithium ion migration. Benefiting from this, the electrolyte of this invention exhibits higher ionic conductivity (4.5 × 10⁻⁶ eV). -4 S cm -1 and a lower activation energy for migration (5.1 kJ mol) -1 ), and the ion transport number was significantly improved.

[0039] (3) By introducing the urea-based side chain structure, this invention not only optimizes internal ion transport but also simultaneously improves the electrochemical stability of the electrolyte and the performance of battery applications. The modified solid polymer electrolyte exhibits excellent high-voltage resistance and can be matched with high-voltage cathode systems. Among them, the fluorophenyl side chain, with its excellent reducing ability, can promote the formation of a stable solid electrolyte interface film rich in LiF and Li3N components during cycling, enabling the electrolyte to withstand voltages up to 5.3 V. The battery assembled with the lithium iron phosphate cathode exhibits excellent capacity retention and long-term cycling stability in cycle tests. The battery prepared based on the fluorophenyl side chain solid electrolyte still retains 100% capacity after 500 cycles, and the specific capacity still remains at 112 mAh g at a high rate of 5 C. -1 This demonstrates the practical value of the present invention in improving the overall performance of solid-state batteries and provides a feasible technical solution for high-performance solid-state polymer electrolyte materials.

[0040] (4) In this invention, the side chain monomer synthesis route is simple, and the solid polymer electrolyte is prepared by thermally initiated in-situ polymerization. The process is economical, the equipment is highly adaptable, and it has the potential for practical production application. Attached Figure Description

[0041] Figure 1 The above is the 1H NMR spectrum of the side-chain monomer synthesized in Example 1 of this invention; Figure 2 The NMR fluorine spectrum of the side-chain monomer synthesized in Example 1 of this invention; Figure 3 The 1H NMR spectrum of ethylene carbonate used in a method for modifying a weak lithium-ion solvated solid polymer electrolyte containing urea side chains. Figure 4 The hydrogen nuclear magnetic resonance spectrum of ethylene glycol dimethacrylate used in a method for modifying a weak lithium-ion solvated solid polymer electrolyte containing urea side chains. Figure 5 The above is the 1H NMR spectrum of the side-chain monomer synthesized in Example 2 of this invention; Figure 6 The above is the 1H NMR spectrum of the side-chain monomer synthesized in Example 3 of this invention; Figure 7 The radial distribution function and coordination number diagram obtained by molecular dynamics simulation in Embodiment 1 of the present invention are shown. Figure 8 The radial distribution function and coordination number diagram of Comparative Example 1 of this invention were obtained through molecular dynamics simulation; Figure 9 The radial distribution function and coordination number diagram obtained by molecular dynamics simulation in Embodiment 2 of the present invention are shown. Figure 10The radial distribution function and coordination number diagram obtained by molecular dynamics simulation in Example 3 of this invention are shown. Figure 11 The side-chain monomer synthesized in Example 1 of this invention is a TFSI - Adsorption model diagram; Figure 12 This is a model diagram of the adsorption of TFSI- by ethylene carbonate in a weak lithium-ion solvation solid polymer electrolyte modification method containing urea side chains. Figure 13 The side-chain monomers synthesized in Example 2 of this invention are TFSI - Adsorption model diagram; Figure 14 The side-chain monomer synthesized in Example 3 of this invention is a TFSI - Adsorption model diagram; Figure 15 The images show the original SEM images of the membrane used in a method for modifying a weak lithium-ion solvated solid polymer electrolyte containing urea side chains, and the SEM images of the polymer electrolyte after in-situ polymerization inside the membrane. Figure 16 The following are the bulk impedance diagrams of the solid polymer electrolyte in Example 1 of the present invention at different temperatures; Figure 17 This is a bulk impedance diagram of the solid polymer electrolyte in Comparative Example 1 of the present invention at different temperatures; Figure 18 The following are the bulk impedance diagrams of the solid polymer electrolyte in Example 2 of the present invention at different temperatures; Figure 19 The following are the bulk impedance diagrams of the solid polymer electrolyte in Example 3 of the present invention at different temperatures; Figure 20 This is a bulk impedance diagram of the solid polymer electrolyte in Comparative Example 2 of the present invention at different temperatures; Figure 21 This is a linear sweep voltammetry curve of the solid polymer electrolyte in Example 1 of the present invention; Figure 22 This is a linear sweep voltammetry curve of the solid polymer electrolyte in Comparative Example 1 of the present invention; Figure 23 This is a linear sweep voltammetry curve of the solid polymer electrolyte in Example 2 of the present invention; Figure 24 This is a linear sweep voltammetry curve of the solid polymer electrolyte in Example 3 of the present invention; Figure 25 The graph shows the efficiency-specific capacity curve of the lithium iron phosphate half-cell prepared in Example 1 of this invention under 0.5 C cycling. Figure 26The graph shows the efficiency-specific capacity curve of the lithium iron phosphate half-cell prepared in Comparative Example 1 of this invention under 0.5 C cycling. Figure 27 The efficiency-specific capacity curve of the lithium iron phosphate half-cell prepared in Example 2 of this invention under 0.5 C cycling. Figure 28 The efficiency-specific capacity curve of the lithium iron phosphate half-cell prepared in Example 3 of the present invention under 0.5 C cycling. Figure 29 Efficiency-specific capacity curves of the lithium iron phosphate half-cell prepared in Example 1 of the present invention after rate cycling test. Figure 30 This is the constant current polarization diagram of the lithium symmetric battery prepared in Example 1 of the present invention during cycling; Figure 31 This is the constant current polarization diagram of the lithium symmetric battery prepared in Comparative Example 1 of the present invention during cycling. Detailed Implementation

[0042] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.

[0043] Unless otherwise specified, the reagents, methods, instruments, and equipment used in this invention are conventional in the art. Unless otherwise specified, the reagents and materials used in the following examples are all commercially available.

[0044] Experimental drugs Experimental instruments Example 1 Isocyanate methacrylate and 4-fluorobenzylamine were dissolved in dichloromethane in a molar ratio of 1:1. Triethylamine, accounting for 1 wt% of the reactants, was added. After the reaction was completed, deionized water was added to quench the reaction. The product was collected by recrystallization (the solvent was dichloromethane:n-hexane in a volume ratio of 2:1). After freeze-drying, the side-chain monomer was obtained. Ethylene ethylene carbonate (VEC), ethylene glycol dimethacrylate (EGDMA), and the side-chain monomer were mixed evenly in a molar ratio of 100:3:3. LiTFSI, accounting for 20 wt% of the polymer solution, and azobisisobutyronitrile, accounting for 1 wt% of the polymer solution, were added and mixed evenly for later use. The negative electrode shell was placed first, and the battery was assembled in the following order: Li sheet, polymer electrolyte, separator, polymer electrolyte, positive electrode sheet, and positive electrode shell. The positive electrode is prepared as follows: lithium iron phosphate, PVDF, and conductive carbon black are dissolved in N-methylpyrrolidone in a ratio of 8:1:1, coated onto aluminum foil, vacuum dried, and cut into 0.6 cm diameter discs using an electrode punching machine. The polymer electrolyte added to the battery is 40 μL. After battery assembly, it is sealed using a coin cell sealing machine, then left to stand for 12 h. After standing, it is placed in an oven at 70℃ for thermally initiated polymerization for 10 h.

[0045] Example 2 Isocyanate methacrylate and benzylamine were dissolved in dichloromethane in a molar ratio of 1:1. Triethylamine (1 wt% of the reactants) was added, and after the reaction was complete, deionized water was added to quench the reaction. The product was then recrystallized (using dichloromethane and n-hexane in a volume ratio of 2:1) and collected. After freeze-drying, the side-chain monomer was obtained. Ethylene carbonate, ethylene glycol dimethacrylate, and the side-chain monomer were mixed evenly in a molar ratio of 100:3:3. 20 wt% LiTFSI and 1 wt% azobisisobutyronitrile (AIBN) of the polymer solution were added and mixed evenly for later use. The negative electrode shell was placed first, and the battery was assembled in the following order: Li sheet, polymer electrolyte, separator, polymer electrolyte, positive electrode sheet, and positive electrode shell. The positive electrode sheet was prepared as follows: Lithium iron phosphate, PVDF, and conductive carbon black were dissolved in N-methylpyrrolidone in a molar ratio of 8:1:1, coated onto aluminum foil, vacuum dried, and cut into 0.6 cm diameter discs using an electrode cutting machine. The amount of polymer electrolyte added to the battery is 40μL. After the battery is assembled, it is sealed using a button cell sealing machine and then left to stand for 12 hours. After standing, it is placed in an oven at 70℃ for thermally initiated polymerization for 10 hours.

[0046] Example 3 Isocyanate methacrylate and n-propylamine were dissolved in dichloromethane in a molar ratio of 1:1. Triethylamine (1 wt% of the reactants) was added. After the reaction was complete, deionized water was added to quench the reaction. The product was recrystallized (dichloromethane:n-hexane volume ratio of 2:1) and collected. After freeze-drying, the side-chain monomer was obtained. Ethylene carbonate, ethylene glycol dimethacrylate, and the side-chain monomer were mixed evenly in a molar ratio of 100:3:3. LiTFSI (20 wt% of the polymer solution) and azobisisobutyronitrile (1 wt% of the polymer solution) were added and mixed evenly for later use. The negative electrode shell was placed first, and the battery was assembled in the following order: Li sheet, polymer electrolyte, separator, polymer electrolyte, positive electrode sheet, and positive electrode shell. The positive electrode sheet was prepared as follows: Lithium iron phosphate, PVDF, and conductive carbon black were dissolved in N-methylpyrrolidone in a molar ratio of 8:1:1, coated onto aluminum foil, vacuum dried, and cut into 0.6 cm diameter discs using an electrode cutting machine. The amount of polymer electrolyte added to the battery is 40 μL. After the battery is assembled, it is sealed using a button cell sealing machine, and then left to stand for 12 h. After standing, it is placed in an oven at 70℃ for thermally initiated polymerization for 10 h.

[0047] Comparative Example 1 Ethylene carbonate and ethylene glycol dimethacrylate were mixed evenly in a molar ratio of 100:3. Then, 20 wt% LiTFSI and 1 wt% azobisisobutyronitrile (AIBN) of the polymer solution were added and mixed thoroughly. The negative electrode shell was placed first, and the battery was assembled in the following order: Li sheet, polymer electrolyte, separator, polymer electrolyte, positive electrode sheet, and positive electrode shell. The positive electrode sheet was prepared as follows: lithium iron phosphate, PVDF, and conductive carbon black were dissolved in N-methylpyrrolidone in an 8:1:1 ratio, coated onto aluminum foil, vacuum dried, and cut into 0.6 cm diameter discs using an electrode cutting machine. The polymer electrolyte added to the battery was 40 μL. After battery assembly, it was sealed using a button cell sealing machine, then allowed to stand for 12 hours. After standing, it was placed in an oven at 70°C for thermally initiated polymerization for 10 hours.

[0048] Comparative Example 2 Isocyanate methacrylate and 2-fluoroethylamine were dissolved in dichloromethane in a molar ratio of 1:1. Triethylamine, accounting for 1 wt% of the reactants, was added. After the reaction was completed, deionized water was added to quench the reaction. The product was collected by recrystallization (the solvent was dichloromethane:n-hexane in a volume ratio of 2:1). After freeze-drying, the side-chain monomer was obtained. Ethylene carbonate (VEC), ethylene glycol dimethacrylate (EGDMA), and the side-chain monomer were mixed evenly in a molar ratio of 100:3:3. LiTFSI, accounting for 20 wt% of the polymer solution, and azobisisobutyronitrile, accounting for 1 wt% of the polymer solution, were added and mixed evenly for later use. The negative electrode shell was placed first, and the battery was assembled in the following order: Li sheet, polymer electrolyte, separator, polymer electrolyte, positive electrode sheet, and positive electrode shell. The positive electrode is prepared as follows: lithium iron phosphate, PVDF, and conductive carbon black are dissolved in N-methylpyrrolidone in a ratio of 8:1:1, coated onto aluminum foil, vacuum dried, and cut into 0.6 cm diameter discs using an electrode die-cutting machine. The polymer electrolyte added to the battery is 40 μL. After battery assembly, it is sealed using a coin cell sealing machine, then left to stand for 12 hours. After standing, it is placed in an oven at 70°C for thermally initiated polymerization for 10 hours.

[0049] Figure 1 This is the 1H NMR spectrum of the side-chain monomer synthesized in Example 1 of this invention. The structural characteristics of the side-chain monomer were confirmed by the 1H NMR spectrum.

[0050] Figure 2 This is the NMR fluorine spectrum of the side-chain monomer synthesized in Example 1 of this invention. The NMR fluorine spectrum further confirmed the structural characteristics of the side-chain monomer.

[0051] Figure 3 This is the 1H NMR spectrum of ethylene carbonate used in this invention. The 1H NMR spectrum confirms the structural characteristics of the ethylene carbonate used.

[0052] Figure 4 This is the 1H NMR spectrum of ethylene glycol dimethacrylate used in this invention. The structural characteristics of the ethylene glycol dimethacrylate used are confirmed by the 1H NMR spectrum.

[0053] Figure 5 This is the 1H NMR spectrum of the side-chain monomer synthesized in Example 2 of this invention. The 1H NMR spectrum confirmed the structural characteristics of the side-chain monomer.

[0054] Figure 6 This is the 1H NMR spectrum of the side-chain monomer synthesized in Example 3 of this invention. The 1H NMR spectrum confirmed the structural characteristics of the side-chain monomer.

[0055] Figure 7This is the radial distribution function and coordination number diagram obtained by molecular dynamics simulation in Example 1 of the present invention. The polymer segments and TFSI in the solvation structure of lithium ions are shown. - The ratio of 1.4:1 indicates that the introduction of this side chain effectively improved the solvation environment of lithium ions, weakened the strong solvation effect of the polymer segment on lithium ions, and increased the TFSI in the solvation structure. - The ratio of these factors is beneficial for forming a stable electrode / electrolyte interface layer.

[0056] Figure 8 This is the radial distribution function and coordination number diagram obtained by molecular dynamics simulation for Comparative Example 1 of the present invention. The polymer segments and TFSI in the solvated structure of lithium ions are shown. - The ratio is 1.8:1, indicating that the polymer segment has the strongest solvation effect on lithium ions when no side chain is introduced. In the solvation structure, TFSI... - The lowest level of participation is not conducive to the rapid migration of lithium ions and the construction of the stable electrode / electrolyte interface layer.

[0057] Figure 9 This is the radial distribution function and coordination number diagram obtained through molecular dynamics simulation in Example 2 of the present invention. The polymer segments and TFSI in the solvation structure of lithium ions are shown. - The ratio was 1.5:1. Compared with the side chain synthesized in Example 1, the side chain synthesized in Example 2 lacked fluorine atoms, which led to an improvement in the solvation effect of the polymer segment on lithium ions compared with Example 1. The rapid migration ability of ions was limited by the polymer segment, indicating that the introduction of fluorine atoms can effectively reduce the strong solvation effect of the polymer segment on lithium ions.

[0058] Figure 10 This is the radial distribution function and coordination number diagram obtained by molecular dynamics simulation in Example 3 of the present invention. The polymer segments and TFSI in the solvated structure of lithium ions are shown. - The ratio was 1.6:1. Compared with the side chains synthesized in Examples 1 and 2, the side chains synthesized in Example 3 lacked fluorophenyl groups, which led to an improvement in the solvation effect of the polymer chain on lithium ions compared with Examples 1 and 2. This indicates that the introduction of benzene rings and fluorine atoms can effectively reduce the strong solvation effect of polymer chain on lithium ions.

[0059] Figure 11 The side-chain monomer synthesized in Example 1 of this invention is a TFSI - The adsorption model diagram shows that the side-chain monomer anchors TFSI through urea group hydrogen bonds and electron-deficient π-electron clouds. -The adsorption energy for TFSI- is -1.34 eV. The highest adsorption energy indicates that it has a stronger adsorption and anchoring effect on lithium salt anions, which is conducive to promoting lithium ion migration and reducing the polarization level during battery cycling.

[0060] Figure 12 Ethylene carbonate for TFSI - Adsorption model diagram of ethylene carbonate for TFSI. - The adsorption energy is -0.95 eV. Compared with the side-chain monomers synthesized in Examples 1, 2 and 3, its adsorption anchoring effect on lithium salt anions is the weakest, indicating that its ability to limit polarization during battery cycling is limited.

[0061] Figure 13 The side-chain monomers synthesized in Example 2 of this invention are TFSI - The adsorption model diagram is shown. The adsorption energy of this side-chain monomer for TFSI- is -1.26 eV. Compared with the side-chain monomer synthesized in Example 1, the side-chain monomer synthesized in Example 2 lacks a fluorine atom, and its adsorption energy for TFSI- is... - Its adsorption and anchoring ability has decreased.

[0062] Figure 14 The side-chain monomer synthesized in Example 3 of this invention is a TFSI - The adsorption model diagram is shown. The adsorption energy of this side-chain monomer for TFSI- is -1.13 eV. Compared with the side-chain monomers synthesized in Examples 1 and 2, the side-chain monomer synthesized in Example 3 lacks a fluorophenyl group, and its adsorption energy for TFSI- is... - Its adsorption and anchoring ability is further reduced.

[0063] Figure 15 The images show the original SEM image of the separator used during battery assembly in Example 1, and the SEM image of the polymer electrolyte after in-situ polymerization inside the separator. The SEM images show that after in-situ polymerization, the polymer electrolyte uniformly fills the porous structure within the separator.

[0064] Figure 16 This is a bulk impedance diagram of the solid polymer electrolyte in Example 1 of the present invention at different temperatures. The solid polymer electrolyte synthesized in Example 1 has an impedance of 3.6 Ω and an ionic conductivity of 4.5 × 10⁻⁶ at 25°C. -4 S cm -1 The activation energy is 5.1 kJ / mol. -1 Thanks to the excellent weak solvation effect of the side chain, the synthesized solid polymeric electrolyte exhibits excellent ionic conductivity and activation energy.

[0065] Figure 17The diagram shows the bulk impedance of the solid polymer electrolyte in Comparative Example 1 of this invention at different temperatures. The solid polymer electrolyte synthesized in Comparative Example 1 has an impedance of 58.8 Ω at 25°C and an ionic conductivity of 2.8 × 10⁻⁶. -5 S cm -1 The activation energy is 9.2 kJ / mol. -1 In solid polymer electrolytes without side chain introduction, lithium-ion migration is hindered, ionic conductivity is low, and lithium-ion migration requires overcoming greater obstacles.

[0066] Figure 18 This is a bulk impedance diagram of the solid polymer electrolyte in Example 2 of the present invention at different temperatures. The solid polymer electrolyte synthesized in Example 2 has an impedance of 8.7 Ω and an ionic conductivity of 1.9 × 10⁻⁶ at 25 °C. -4 S cm -1 The activation energy is 7.1 kJ / mol. -1 Compared to the examples, the solid polymer electrolyte synthesized in Example 2 has a lower ionic conductivity due to the absence of fluorine atoms in the side chain, and the energy barrier that lithium ions need to overcome for migration is increased.

[0067] Figure 19 This is a bulk impedance diagram of the solid polymer electrolyte in Example 3 of the present invention at different temperatures. The solid polymer electrolyte synthesized in Example 3 has an impedance of 14.3 Ω at 25°C and an ionic conductivity of 1.1 × 10⁻⁶. -4 S cm -1 The activation energy is 7.3 kJ / mol. -1 Compared to Examples 1 and 2, due to the absence of side-chain fluorophenyl groups, the ionic conductivity of the solid polymer electrolyte synthesized in Example 3 is further reduced, and the energy barrier that lithium ions need to overcome is further increased.

[0068] Figure 20 The figures show the bulk impedance of the solid polymer electrolyte in Comparative Example 2 of this invention at different temperatures. The solid polymer electrolyte synthesized in Comparative Example 2 has an impedance of 28.9 Ω and an ionic conductivity of 5.6 × 10⁻⁶ at 25 °C. -5 S cm -1 The activation energy is 7.5 kJ / mol. -1 Compared to Examples 1, 2 and 3, the introduction of fluorinated alkane side chains makes it difficult to provide a weak solvation effect similar to that of phenyl / fluorophenyl. At the same time, the lithium-phobic properties of F atoms also make them weaker than alkane segments in ion transport. Therefore, the ionic conductivity of the solid polymer electrolyte synthesized in Comparative Example 2 is reduced, and the energy barrier that lithium ions need to overcome is increased.

[0069] Both Examples 1 and 2 belong to aromatic side-chain systems. In this system, the phenyl group can construct a weak solvation environment, and the introduction of the F atom further enhances the electron-withdrawing effect of the aromatic side chain, reduces the electron cloud density of the side chain, weakens the interaction between lithium ions and polymer side chains, and makes lithium ions more likely to undergo desolvation and interchain transitions. Therefore, Example 1 exhibits higher ionic conductivity and a lower lithium ion migration barrier.

[0070] Comparative Example 2 and Example 3 belong to aliphatic side-chain systems. In this system, ordinary alkyl groups mainly promote polymer chain movement by increasing chain flexibility and free volume, while fluoroalkyl groups, due to their high CF bond polarization, increased chain rigidity, strong lithium-repellency, and tendency to form fluorine-rich microregions, weaken the polymer chain movement capability and the continuity of lithium-ion migration channels. Their adverse effects outweigh the weak solvation effect, thus Comparative Example 2 exhibits lower ionic conductivity and a higher lithium-ion migration barrier. These differences stem from the different dominant mechanisms of the fluorine atom in aromatic and aliphatic chain systems; the former is dominated by electronic effects, while the latter is dominated by chain segment movement and microphase structure effects.

[0071] Figure 21 This is a linear sweep voltammetry curve of the solid polymer electrolyte in Example 1 of the present invention. Thanks to the excellent reducing ability of the side chains, it is beneficial to form a solid electrolyte interface film rich in LiF and Li3N components, and the prepared solid polymer electrolyte can withstand voltages up to 5.3 V.

[0072] Figure 22 This is a linear sweep voltammetry curve of the solid polymer electrolyte in Comparative Example 1 of this invention. Due to the lack of side chains, the solid electrolyte interfacial membrane has insufficient functionality, and the prepared solid polymer electrolyte can only withstand a voltage of 4.8 V.

[0073] Figure 23 This is a linear sweep voltammetry curve of the solid polymer electrolyte in Example 2 of the present invention. Compared with the example, due to the absence of fluorine atoms in the side chain, its side chain reduction ability is weakened, the stability of the solid electrolyte interfacial film is reduced, and the obtained solid polymer electrolyte can withstand a voltage of 5.1 V.

[0074] Figure 24 This is a linear sweep voltammetry curve of the solid polymer electrolyte in Example 3 of the present invention. Compared with Examples 1 and 2, due to the absence of the fluorophenyl side chain groups, its side chain reduction ability is further weakened, the stability of the solid electrolyte interfacial film is further reduced, and the obtained solid polymer electrolyte can withstand a voltage of 5.0 V.

[0075] Figure 25This is an efficiency-specific capacity curve of the lithium iron phosphate half-cell prepared in Example 1 of this invention at 0.5 C. Thanks to the rapid lithium-ion migration induced by the side chain and the stable solid electrolyte interface film, the prepared battery retains 100% of its capacity after 500 cycles.

[0076] Figure 26 This is an efficiency-specific capacity curve of the lithium iron phosphate half-cell prepared in Comparative Example 1 of this invention at 0.5 C. Due to the lack of side chain introduction, ion migration is hindered, and the solid electrolyte interface film is unstable. The prepared battery retains 70% of its capacity after 500 cycles.

[0077] Figure 27 This is an efficiency-specific capacity curve of the lithium iron phosphate half-cell prepared in Example 2 of the present invention at 0.5 C. Compared with Example 1, the absence of fluorine atoms in the side chain leads to a decrease in the lithium-ion migration rate of the solid polymer electrolyte and the stability of the solid electrolyte interface film. The prepared battery retains 91% of its capacity after 500 cycles.

[0078] Figure 28 This is an efficiency-specific capacity curve of the lithium iron phosphate half-cell prepared in Example 3 of the present invention at 0.5 C. Compared with Examples 1 and 2, the absence of the fluorophenyl side chain leads to a decrease in the lithium-ion migration rate of the solid polymer electrolyte and the stability of the solid electrolyte interface film. The capacity retention rate of the prepared battery is 71% after 500 cycles.

[0079] Figure 29 The efficiency-specific capacity curves for the lithium iron phosphate half-cell prepared in Example 1 of this invention are shown in the figure. Thanks to the weak solvation ability of the polymer segments for lithium ions, it exhibits excellent high-rate cycling capability. It can maintain stable cycling at 5 C, and the specific capacity remains at 112 mAh g⁻¹ at 5 C. -1 .

[0080] Figure 30 This is the constant-current polarization diagram of the lithium symmetric battery prepared in Example 1 of the present invention during cycling. The prepared lithium symmetric battery was cyclically polarized at 0.2 mA cm⁻¹. -2 0.2 mAh cm -2 Under stable cycling conditions for 2000 h, the polarization voltage is approximately 0.14 V.

[0081] Figure 31 This is the constant-current polarization diagram of the lithium symmetric battery prepared in Comparative Example 1 of this invention during cycling. The prepared lithium symmetric battery was tested at 0.2 mA cm⁻¹. -2 0.2 mAh cm -2 Under certain conditions, the cyclic stability is poor, and the polarization voltage is approximately 0.40 V.

[0082] In summary, this invention provides a method for modifying a weakly lithium-ion solvated solid polymer electrolyte containing urea-based side chains, which solves the problems of low lithium-ion migration rate, poor high-voltage resistance, and unstable SEI film (solid electrolyte interface film) in existing solid polymer electrolytes. The specific steps are as follows: Isoethyl methacrylate and 4-fluorobenzylamine are dissolved in dichloromethane in a molar ratio of 1:1. Triethylamine, accounting for 1 wt% of the reactants, is added. After the reaction is completed, deionized water is added to quench the reaction. The product is collected by recrystallization (the solvent is dichloromethane: n-hexane in a volume ratio of 2:1). After freeze-drying, the side-chain monomer is obtained. Ethylene carbonate, ethylene glycol dimethacrylate and the side-chain monomer are mixed evenly in a molar ratio of 100:3:3. LiTFSI, accounting for 20 wt% of the polymer solution and azobisisobutyronitrile, are added and mixed evenly for later use. The negative electrode shell is placed, and the battery is assembled in the following order: lithium sheet, polymer electrolyte, separator, polymer electrolyte, positive electrode sheet and positive electrode shell. The amount of polymer electrolyte added is 40 μL. After the battery is assembled, it is allowed to stand for 12 h. After standing, it is placed in an oven at 70℃ for thermally initiated polymerization for 10 h to obtain a lithium battery containing a solid polymer electrolyte. Compared with existing technologies, this invention promotes the rapid migration of lithium ions in solid polymer electrolytes, enhances high voltage resistance, forms a more stable SEI film, optimizes the polarization voltage level during battery cycling, and improves the specific capacity and capacity retention during battery charging and discharging.

[0083] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A weakly lithium-ion solvable solid polymer electrolyte containing urea side chains, characterized in that, Includes the polymer matrix and the lithium salt distributed therein; The polymer matrix is ​​formed by in-situ polymerization and crosslinking of side-chain monomers, ethylene ethylene carbonate, and ethylene glycol dimethacrylate; the structural formula of the side-chain monomers is shown in general formula (I): General formula (Ⅰ); R1 includes any one of phenyl, fluorophenyl, and alkyl.

2. The weakly lithium-ion solvated solid polymer electrolyte containing urea side chains according to claim 1, characterized in that, R1 includes either phenyl or fluorophenyl.

3. A method for preparing a weakly lithium-ion solvated solid polymer electrolyte containing urea-group side chains as described in any one of claims 1-2, characterized in that, Includes the following steps: S1. Preparation of side-chain monomers: Isoethyl methacrylate and amine monomers are dissolved in an organic solvent, a catalyst is added to catalyze the reaction, deionized water is added to quench the reaction after the reaction is completed, the product is collected by recrystallization, and the side-chain monomers are obtained by freeze drying. S2. Preparation of solid polymer electrolyte precursor solution: Ethylene carbonate, ethylene glycol dimethacrylate and the side chain monomer obtained in step S1 are mixed evenly, and then lithium salt and azobisisobutyronitrile are added and mixed evenly to obtain the solid polymer electrolyte precursor solution. S3. In-situ polymerization to form solid polymer electrolyte: The solid polymer electrolyte precursor solution is injected into the lithium-ion battery, and after standing for a period of time, an in-situ polymerization and cross-linking reaction is carried out by thermal initiation to form the solid polymer electrolyte in-situ inside the lithium-ion battery.

4. The method for preparing a weakly lithium-ion solvable solid polymer electrolyte with urea-group side chains according to claim 3, characterized in that, In step S1, the amine monomer includes any one of benzylamine, 4-fluorobenzylamine, or alkylamine.

5. The method for preparing a weakly lithium-ion solvable solid polymer electrolyte with urea-group side chains according to claim 3, characterized in that, In step S1, the organic solvent includes one or more of dichloromethane and acetonitrile, and the catalyst includes one or more of triethylamine and dibutyltin dilaurate.

6. The method for preparing a weakly lithium-ion solvable solid polymer electrolyte with urea-group side chains according to claim 3, characterized in that, In step S1, the molar ratio of isocyanate methacrylate to amine monomer is 1-5:1-5, the catalyst is 0.1-10 wt% of the sum of the mass of isocyanate methacrylate and amine monomer, the reaction temperature is 0-30℃, and the reaction time is 6-12 h; the solvent used for recrystallization is a mixed solvent of dichloromethane and n-hexane, and the volume ratio of dichloromethane to n-hexane is 1-4:1-4.

7. The method for preparing a weakly lithium-ion solvable solid polymer electrolyte with urea-group side chains according to claim 3, characterized in that, In step S2, the molar ratio of ethylene carbonate: ethylene glycol dimethacrylate: side chain monomer is 100:1-5:0-5.

8. The method for preparing a weakly lithium-ion solvable solid polymer electrolyte with urea-group side chains according to claim 3, characterized in that, In step S2, the mass ratio of the lithium salt to the solid polymer electrolyte precursor solution is 1:1-10, and the mass ratio of the azobisisobutyronitrile to the solid polymer electrolyte precursor solution is 0.01-0.1:1; the lithium salt includes any one of lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate, lithium bis(difluorosulfonyl)imide, lithium bis(oxalate borate), and lithium tetrafluoroborate.

9. The method for preparing a weakly lithium-ion solvable solid polymer electrolyte with urea-group side chains according to claim 3, characterized in that, In step S3, the settling time is 1-24 h, and the temperature for the thermally initiated in-situ polymerization crosslinking reaction is 50-80℃, and the time is 6-10 h.

10. The application of a weakly lithium-ion solvated solid polymer electrolyte containing urea-group side chains as described in any one of claims 1-2 in a lithium-ion battery.